Soil retention processes of diuron, hexazinone and sulfometuron-methyl herbicides applied isolated and in mixture - Carneiro, Gabriella Daier Oliveira Pessoa (Universidade Federal Rural do Semi-Árido, 2020)
The mixture of herbicides is an important tool used in the control of weeds in different cultures. However, interactions between herbicide molecules can alter their retention processes in the soil and, consequently, their effectiveness in controlling weeds and potential for environmental impact. In this research, the effects of the mixture on the kinetics and intensity of sorption and desorption in the soil of diuron, hexazinone and sulfometuron-methyl applied separately were evaluated. The sorption kinetics was estimaded of isolated and mixed binary and triple herbicides using the pseudo-first order and pseudo-second order models. In the study of sorption and desorption, the Freundlich model was used because it presents a better fit in relation to the Langmuir and Linear models. Regardless of the herbicide, the mixture or the soil, adsorption occurred quickly during the first hour, followed by a much slower stage progressing towards an apparent equilibrium. The model, in general, that best fit the study was pseudo-second order, which consists of adsorption in the monolayer. The concentration absorbed at equilibrium was lower for the binary and ternary mixtures of the herbicides. The adsorption time and the sorption capacity of the herbicides showed the following order of diuron> hexazinone> sulfometuron-methyl in the dystrophic red Oxisol and diuron> sulfometuron-methyl> hexazinone in the red-yellow Oxisol. The binary and ternary combinations between diuron, hexazinone and sulfometuron-methyl reduced the sorption and desorption in the soils compared to the isolated tests of these herbicides. The sorption and desorption of hexazinone in soils is most affected by mixing with other herbicides. Sulfometuronmethyl promotes greater reduction in the sorption of diuron in relation to hexazinone. The mixture between diuron, hexazinone and sulfometuron-methyl increases the availability of these herbicides in the aqueous phase of the soil allowing the use of lower rates in the application compared to isolated applications. Higher availability also indicates a greater potential for environmental contamination via leaching or surface runoff.
Keywords: Sorção; Dessorção; Cinética; Adsorção; Sorption; Desorption; Kinects; Adsorption; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA